Five new OTOF gene mutations and auditory neuropathy. - Zadro, Cristina; Ciorba, Andrea; Fabris, Annalisa; Morgutti, Marcello; Trevisi, Patrizia; Gasparini, Paolo; Martini, Alessandro (Int J Pediatr Otorhinolaryngol, 2010)
OBJECTIVE: Purpose of this paper is to analyse OTOF gene in a series of subjects affected by auditory neuropathy. METHODS: Four children showing mild to profound prelingual deafness, confirmed by the absence of a clear and detectable responses at auditory brainstem responses (ABR), associated with the presence of bilateral OAE, were enrolled in the study. RESULTS AND CONCLUSIONS: Genetic analysis identified five new mutations (a nonsense, a small and a large deletion and two splicing site mutations), and one missense mutation (F1795C) previously described. These results further confirm the role of OTOF gene in auditory neuropathy. In the absence of a context of neurological syndrome, the combination of absent ABR and positive OAE responses should lead to an auditory neuropathy diagnosis and to a mutational screening in OTOF.
Keywords: Auditory Diseases, Central; Deafness; Evoked Potentials, Auditory, Brain Stem; Female; Humans; Male; Membrane Proteins; Mutation; Otoacoustic Emissions, Spontaneous; Polymerase Chain Reaction